Legal Protection of Traditional Knowledge Concept Based Prior Informed Consent and Access Benefit Sharing System - Hafshoh, Fazyla Alyaa; Masyithoh, Novita Dewi; Maksun, Maksun (Walisongo Law Review (Walrev), 2021)
Protection of traditional knowledge in Indonesia has not had effective and adequate legal regulations, so it gives opportunities to irresponsible parties for in a manner unilateral claims and take advantage of the economic function of knowledge; that is, there is the utilization of traditional knowledge without permitting access to utilization and profit sharing fair and balanced. There need to be sui rules generis governing the concept of Prior Informed Consent (PIC) for access permission and appropriate and benefit sharing balanced with the idea of Access and Benefits Sharing System (ABS). This is research doctrinal, with approach statute approach to find out whether there have been regulations and norms governing the protection of traditional knowledge.Perlindungan pengetahuan tradisional di Indonesia belum mempunyai aturan hukum yang efektif dan memadai, sehingga memberikan peluang kepada pihak yang tidak bertanggung jawab untuk secara sepihak mengklaim dan memanfaatkan fungsi ekonomi dari pengetahuan tradisional tersebut, yaitu adanya pemanfaatan pengetahuan tradisional tanpa       adanya izin akses pemanfaatan serta pembagian keuntungan yang adil dan seimbang. Perlu adanya peraturan sui generis yang mengatur tentang konsep Prior Informed Consent (PIC) untuk ijin akses dan pembagian keuntungan yang adil dan seimbang dengan konsep Access and Benefit Sharing System (ABS). Ini merupakan penelitian doktrinal, dengan pendekatan statute approach untuk mengetahui apakah telah ada regulasi dan norma yang mengatur tentang perlindungan tentang pengetahuan tradisional